Bifunctional PdPt bimetallenes for formate oxidation‐boosted water electrolysis - Xi‐Lai Liu; Yu‐Chuan Jiang; Jiang‐Tao Huang; Wei Zhong; Bin He; Pu‐Jun Jin; Yu Chen (Carbon Energy, 2023)
Abstract Small‐molecule electrooxidation‐boosted water electrolysis (WE) is an energy‐saving method for hydrogen (H2) production. Herein, PdPt bimetallenes (PdPt BMLs) are obtained through the simple galvanic replacement reaction. PdPt BMLs reveal 2.93‐fold enhancement in intrinsic electroactivity and 4.53‐fold enhancement in mass electroactivity for the formate oxidation reaction (FOR) with respect to Pd metallenes (Pd MLs) at 0.50 V potential due to the synergistic effect. Meanwhile, the introduction of Pt atoms also considerably increases the electroactivity of PdPt BMLs for hydrogen evolution reaction (HER) with respect to Pd MLs in an alkaline medium, which even exceeds that with the use of commercial Pt nanocrystals. Inspired by the outstanding FOR and HER electroactivity of bifunctional PdPt BMLs, a two‐electrode FOR‐boosted WE system (FOR‐WE) is constructed by using PdPt BMLs as the cathode and the anode. The FOR‐WE system only requires an operational voltage of 0.31 V to achieve H2 production, which is 1.48 V lower than that (ca. 1.79 V) with the use of the traditional WE system.